PENINGKATAN SELF-EFFICACY AKADEMIK MELALUI PSIKOEDUKASI PADA SISWA MTS - Siti Muzaro’atut Dawamah; Cahyaning Suryaningrum; Yuni Nurhamida (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Low academic self-efficacy may hinder students' ability to cope with learning demands, particularly among Islamic junior high school students who simultaneously undertake academic and Qur'an memorization responsibilities. This community service program aimed to strengthen students' academic self-efficacy through a psychoeducational intervention implemented at MTs Unggulan Al Bahroin. The program was conducted through a series of activities, including needs assessment, delivery of self-efficacy-based learning materials, interactive discussions, self-reflection sessions, evaluation, and follow-up mentoring to support the application of the acquired knowledge in daily learning practices. Program evaluation employed a pre-test and post-test design to examine changes in participants' academic self-efficacy following the intervention. The implementation results indicated that the psychoeducational program enhanced participants' understanding of academic self-efficacy, strengthened their confidence in managing academic tasks, and fostered greater learning motivation, perseverance, and readiness to address academic challenges. Furthermore, the program produced a practical psychoeducational model that can serve as an alternative student support program for promoting psychological readiness and academic resilience in both school and Islamic boarding school settings. ABSTRAK Rendahnya self-efficacy akademik menjadi salah satu faktor yang dapat menghambat kemampuan siswa dalam menghadapi tuntutan pembelajaran, terutama pada siswa MTs yang juga menjalani peran sebagai santri tahfidz dengan beban akademik dan keagamaan secara bersamaan. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan self-efficacy akademik melalui program psikoedukasi yang diselenggarakan di MTs Unggulan Al Bahroin. Program dilaksanakan melalui tahapan identifikasi kebutuhan, penyampaian materi berbasis teori self-efficacy, diskusi interaktif, refleksi diri, evaluasi, dan pendampingan untuk mendukung penerapan materi dalam aktivitas belajar. Evaluasi program dilakukan menggunakan desain pre-test dan post-test untuk mengidentifikasi perubahan self-efficacy akademik peserta setelah mengikuti kegiatan. Hasil pelaksanaan menunjukkan bahwa program psikoedukasi mampu meningkatkan pemahaman peserta mengenai konsep self-efficacy akademik, memperkuat keyakinan terhadap kemampuan dalam menyelesaikan tugas belajar, serta mendorong berkembangnya motivasi, ketekunan, dan kesiapan dalam menghadapi tantangan akademik. Selain memberikan dampak positif terhadap peserta, kegiatan ini menghasilkan model psikoedukasi yang dapat diimplementasikan sebagai alternatif program pendampingan dalam mendukung penguatan kapasitas psikologis siswa di lingkungan sekolah maupun pesantren.